Borobudur Story Relief, A Silent Visual Narration - Primadi Tabrani (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Our research team found out that prehistory, primitive, traditional and children drawings havenearly the